The exhaustion of industrial property rights in african intellectual property organization (OAPI) - (:unkn) unknown (My University, 2013)
The African intellectual property Organization (AIPO) consecrated the theory of exhaustion right since the revision of 1999. It puts the legal conditions of the theory. It seems that these conditions, which are considered as a limitation of the monopolistic right of the t industrial property owners, after all, protect this right and give consistency to it. Through the right of commercialization that is limited to the national territory for marks and to the regional territory for patents, the African legislator keeps the products from free-trade. Nevertheless, the existence of the free-trade areas like UEMOA and CEMAC could enlarge the domain of the trade of the merchandises. The theory of exhaustion is stringent, without a far-reaching influence. It is consistent with the principle of the protection of the intellectual property rights that is of paramount importance. The international exhaustion is rejected even though it can be a means of the regulation of the free trade of the marked or patented products. So, the impact of international exhaustion may be itself relativized. The African countries have to search the transfer of technology that appears as the one means which can transform the industrial property in Africa.
Keywords: African Research